Bibliometric mapping of urban ecology and urban decline (2010-2024): Trends, themes and network structures - Pogrmić Zorica (Zbornik radova Departmana za geografiju, turizam i hotelijerstvo, 2025)
This study presents a bibliometric mapping of research on urban ecology and urban decline from 2010 to 2024, identifying key publication trends, thematic structures, and network dynamics. Although a significant increase in research output was hypothesized, the Mann-Kendall trend test (p = 0.262) did not confirm a consistent upward trend. Sub-period analyses also showed no significant monotonic patterns, though publication peaks in 2014, 2018, and 2021 suggest research surges linked to global and European initiatives. VOSviewer cluster analysis highlighted dominant themes centred on spatial and demographic aspects of decline, such as brownfields and land use, shifting after 2016 toward ecological, participatory, and community-focused approaches. Overlay visualizations indicate a move from descriptive to interventionist frameworks, reflecting changes in urban policy. Co-authorship and citation networks reveal the central role of European institutions, especially German researchers, in shaping the field. Scholars like Dagmar Carole Haase serve as key nodes in interdisciplinary collaboration. Despite thematic fragmentation, citation patterns suggest conceptual convergence around critical-interpretive and techno-ecological paradigms. Overall, the findings show a growing integration of transdisciplinary perspectives in line with sustainable urban transformation goals.